PENGARUH SUKU BUNGA, JUMLAH UANG BEREDAR, NILAI TUKAR, CADANGAN DEVISA, DAN PERTUMBUHAN EKONOMI TERHADAP INFLASI DI INDONESIA 2009 - 2024 - Vazco Bawuka; Mauna Th. B. Maramis; Dennij Mandeij (Jurnal Riset Multidisiplin Edukasi, 2026)
Inflation is a macroeconomic indicator that reflects price stability and people's purchasing power and is the main target of economic policy in Indonesia. However, the achievement of inflation targets is often influenced by various monetary factors and economic fundamentals. This study aims to analyze the influence of interest rates, money supply (M2), rupiah exchange rate, foreign exchange reserves, and economic growth on inflation in Indonesia during the period 2009–2024. The research uses a quantitative approach with secondary time series data obtained from the Central Statistics Agency (BPS) and Bank Indonesia. The analysis was carried out using multiple linear regression with t-test, F-test, coefficient of determination (R²), and classical assumption testing to ensure the validity of the model. The results show that only interest rates have a significant effect on inflation, while the money supply (M2), exchange rate, foreign exchange reserves, and economic growth do not show a significant influence. Nevertheless, simultaneously all variables have a significant effect on inflation. These findings show that controlling inflation requires coordination of various policy instruments, not just relying on interest rates. Therefore, synergy between Bank Indonesia and the government is an important factor in maintaining macroeconomic stability. The results of this study are expected to be a reference for policymakers and further research related to inflation dynamics in Indonesia.